RISE: Tree wood density assessment using micro drilling device, resistograph for sustainable forest management operation / Ts. Jacqueline Joseph - Joseph, Jacqueline (Office of the Deputy Vice-Chancellor (Research & Innovation), 2022)
Wood density (WD) is one of the crucial predictor variables aside from tree diameter and height, which serves to quantify the forest above-ground biomass (AGB) and carbon stocks. Hence, carbon stocks reports require robust data and transparent information on WD to be provided to United Nations Framework Convention on Climate Change (UNFCC). Notably, acquiring in-situ field WD of live trees could be significantly challenging and arduous. Due to this, a non-destructive tool (NDT) is indispensable to predict the WD of trees without jeopardizing the tree itself.